1981
DOI: 10.1002/jbm.820150108
|View full text |Cite
|
Sign up to set email alerts
|

Fixation of porous titanium implants in cortical bone enhanced by electrical stimulation

Abstract: The effect of in vivo electrical stimulation on the interfacial strength between porous titanium implants and cortical bone was studied in mongrel dogs. The interfacial shear strength of the stimulated implants was consistently greater than that of controls. No difference could be observed in the quality of bone ingrowth. The data suggest that the rate and quantity of bone ingrowth were enhanced by electrical stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

1987
1987
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 11 publications
0
22
0
1
Order By: Relevance
“…In this case, mechanically triggered electrical charge separation acts as the prime mechanism during the remodeling of a broken bone, whereby the structure and function of growing bone cells and extracellular structures are infl uenced by piezoelectric and stream potentials (Bassett and Becker, 1962 ;Bassett, 1968 ). It has been shown in clinical studies that the electrical stimulation of bone growth, with the fi elds aligned parallel to the axis of a long bone, acts to reduce the time required for endosteal callus remodeling, and hence speeds up the healing process (Weigert, 1973 ;Weinstein, 1976 ;Colella et al , 1981 ;Berry et al , 1986 ). However, it has also been observed that whilst a pulsed, transverse electric fi eld tended to accelerate the growth of embryonic chick tibiae, a static, non -varying fi eld had no signifi cant effect (Watson et al ., 1975 ).…”
Section: Acceleration Of Bone Growth By An Electric Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, mechanically triggered electrical charge separation acts as the prime mechanism during the remodeling of a broken bone, whereby the structure and function of growing bone cells and extracellular structures are infl uenced by piezoelectric and stream potentials (Bassett and Becker, 1962 ;Bassett, 1968 ). It has been shown in clinical studies that the electrical stimulation of bone growth, with the fi elds aligned parallel to the axis of a long bone, acts to reduce the time required for endosteal callus remodeling, and hence speeds up the healing process (Weigert, 1973 ;Weinstein, 1976 ;Colella et al , 1981 ;Berry et al , 1986 ). However, it has also been observed that whilst a pulsed, transverse electric fi eld tended to accelerate the growth of embryonic chick tibiae, a static, non -varying fi eld had no signifi cant effect (Watson et al ., 1975 ).…”
Section: Acceleration Of Bone Growth By An Electric Fieldmentioning
confidence: 99%
“…In these experiments, a substantially higher maximum shear stress was required to push out of its bony bed an implant subjected to electrical stimulation compared to a control (Colella et al , 1981 ). For this, a commercially pure ( cp ) -titanium cylinder, acting as a cathode, was inserted into the mid -femoral diaphysis of a dog, and segments of kinked Ti wires (acting as anode) were placed in coils around the bone, above and below the implant, such that the electric fi eld lines were directed along the long axis of the femur.…”
Section: Acceleration Of Bone Growth By An Electric Fieldmentioning
confidence: 99%
“…Pushout, pullout and torsional tests are experimental techniques widely used to evaluate shear stiffness and shear strength of the bone implant interface (Colella et al, 1981;Søballe et al, 1990Søballe et al, , 1991aSøballe et al, , b, 1992aSøballe et al, , b, 1993Dhert et al, 1991;Cook et al, 1992;Wang et al, 1996;Overgaard et al, 1997;Lewis et al, 1997;Elmengaard et al, 2005). Despite the numerous pushout studies published in the literature, accurate numerical models to describe the mechanical response of the bone implant interface are still lacking.…”
Section: Introductionmentioning
confidence: 98%
“…Current availability of semiconductors and proper insulat- The effect of in situ electrical stimulation has been studied in experimental models of fracture healing, ostectomy, osteogenic distraction, and implants. [7][8][9] Clinical studies have evaluated its effect on nonunion fracture healing, bone graft attachment to bony defects, and osteoradionecrosis among others. All the above showed that the effect of in situ electrical stimulation varies substantially depending on the intensity of the stimulus, the polarity of the applied current, its duration, whether it is continuous or pulsed, and on the metal used as an electrode.…”
mentioning
confidence: 99%